2018
DOI: 10.1016/j.celrep.2017.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing ZC3H18, a Multi-domain Protein at the Interface of RNA Production and Destruction Decisions

Abstract: SummaryNuclear RNA metabolism is influenced by protein complexes connecting to both RNA-productive and -destructive pathways. The ZC3H18 protein binds the cap-binding complex (CBC), universally present on capped RNAs, while also associating with the nuclear exosome targeting (NEXT) complex, linking to RNA decay. To dissect ZC3H18 function, we conducted interaction screening and mutagenesis of the protein, which revealed a phosphorylation-dependent isoform. Surprisingly, the modified region of ZC3H18 associates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 43 publications
5
42
0
Order By: Relevance
“…The EMBO GTF3C3,GTF3C4,GTF3C5 TXLNA,TNPO1,MAP3K20,PRPF19 CALU,RCN2,HNRNPH1,GANAB WDR62,HIST1H1C,NUMA1,SNRPD2 CCT4, CCT5, CCT8, TCP1 COPG1,COPA,RPS27A CCNA2,CDK2,CDK1 ZNF460,ZNF677,c18orf25 RNH1,SART3, these KZFPs, while perhaps still repressing transcription, do so no longer to block retrotransposition, since their target retroelements have long lost all spreading potential. ZNF765 is recruited over the L1PA5/PA6 promoter region, and two of its interactors stand out as potential regulators of LINE1 transcripts: the RNA-binding proteins interactor ZKSCAN4 and ZC3H18, known to be involved in RNA export, anabolism, and catabolism (Chi et al, 2014;Winczura et al, 2018). Furthermore, L1PA6 and L1PA5 integrants also recruit over their 3 0 half two KZFPs with conventional KAP1-centered interactomes, ZNF382 and ZNF84, for which there is no sign of mutational escape, strongly suggesting that these KZFPs, in spite of their repressor potential, never limited the spread of these retrotransposons.…”
Section: Of 16mentioning
confidence: 99%
“…The EMBO GTF3C3,GTF3C4,GTF3C5 TXLNA,TNPO1,MAP3K20,PRPF19 CALU,RCN2,HNRNPH1,GANAB WDR62,HIST1H1C,NUMA1,SNRPD2 CCT4, CCT5, CCT8, TCP1 COPG1,COPA,RPS27A CCNA2,CDK2,CDK1 ZNF460,ZNF677,c18orf25 RNH1,SART3, these KZFPs, while perhaps still repressing transcription, do so no longer to block retrotransposition, since their target retroelements have long lost all spreading potential. ZNF765 is recruited over the L1PA5/PA6 promoter region, and two of its interactors stand out as potential regulators of LINE1 transcripts: the RNA-binding proteins interactor ZKSCAN4 and ZC3H18, known to be involved in RNA export, anabolism, and catabolism (Chi et al, 2014;Winczura et al, 2018). Furthermore, L1PA6 and L1PA5 integrants also recruit over their 3 0 half two KZFPs with conventional KAP1-centered interactomes, ZNF382 and ZNF84, for which there is no sign of mutational escape, strongly suggesting that these KZFPs, in spite of their repressor potential, never limited the spread of these retrotransposons.…”
Section: Of 16mentioning
confidence: 99%
“…Finally, RNA association of the exosome factors proposed to interact with poly(A) tail such as Pab2 and Red5 is decreased in exosome mutants ( Figure 8D) suggesting that exosome either directly or indirectly contributes to assembly of these factors with RNA. and ZFC3H1 supporting an evolutionary conserved role for these proteins in exosome regulation (80)(81)(82). ZCCHC8 interacts with RNA binding protein RMB7 and helicase MTR4 to form the trimeric Nuclear EXosome Targeting (NEXT) (81,83).…”
Section: Mub1 Regulates Exosome Degradation Of the Stress-induced Mrnasmentioning
confidence: 92%
“…5b). Employing RNA-seq data collected in parallel (53,54) demonstrated that NCBP1 depletion did not show such an exon-content effect on RNA levels (Fig. 5d, Supplementary Fig.…”
Section: Ncbp3 Depletion Causes Exon-number Biased Regulation Of Rna mentioning
confidence: 98%
“…RNA extraction and RNA-seq library preparation upon GFP and NCBP3 depletion were performed as described (53). Total RNAseq of siNCBP3 depletion samples are first reported here, but were collected as part of same experiment described in (53,54).…”
Section: Rna Sequencing (Rna-seq) and Data Analysismentioning
confidence: 99%